Rainfall Trend Analysis Using Non-Parametric Test: A Case Study of Jaffna District, Sri Lanka - Athavan, R. (My University, 2019)
Rainfall is a vital climatic factor which can affect the development and progress of a nation. Analysis of rainfall trend plays a major role in studying the impacts of water resources and agriculture activities. Changes in rainfall and other forms of precipitation will be one of the most critical factors which determine the overall impact of all seasons. The current study is centered to analyse the trends in the annual and seasonal (pre-monsoon, monsoon, post-monsoon) total rainfall at Jaffna district, North of Sri Lanka by using the available 44 years (1972-2015) monthly rainfall data of rain-gauge station at Tirunelveli. The trend analysis was carried out by using Mann-Kendall test and Sen’s slope estimator. The study area is characterized by average rainfall which receives an annual average rainfall of 1298 ± 683 mm but the analysis of long-term trends in the annual rainfall indicates an increasing of the trend (+2.058 mm per year) and annual rainy days which also had insignificantly decreased (-23.625 days per year). The graphical representation of the trend in annual and seasonal rainfall series expressed by Mann-Kendall Zc value seasonally, monsoon (0.017), post-monsoon (0.196) and annual (0.055) are showing positive trend and pre-monsoon (-0.135) depicting negative trend. Sen’s Slope estimator also reflects the increase during the monsoon (0.504), post-monsoon (1.649), annual (2.058) and decreasing in pre-monsoon (-1.967) magnitude of slope in correspondence with the MK test values. Annual and seasonal analysis resembles both positive and negative trend in the area although not significant (P>0.05)
Keywords: Jaffna district; Mann-Kendall test; Sen’s slope estimator; Rainfall trend